Sustainability and Loyalty in Halal Tourism: An Indonesian Perspective - Sukma, Andhi; Chen, Robin; Rachmat, Radhi Abdul Halim; Saputera, Denny (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study introduces new behavioral dimensions, including environmental awareness, ethical service innovation, and tourists’ decision control, in the formation of loyalty and advocacy behavior. Research Objectives: This study examines the contribution of sustainability-oriented factors to Muslim tourist loyalty and recommendation behavior, with satisfaction and intention to revisit serving as mediating variables. Research Methods: A quantitative approach was employed using a structured questionnaire distributed to 460 Muslim tourists. The data were analyzed using structural equation modeling to evaluate the causal relationships among the variables. Empirical Results: Environmental awareness and tourists’ ability to make ethical decisions have a significant influence on loyalty and word-of-mouth behavior. Ethical service innovation enhances customer satisfaction, which in turn contributes to loyalty. Satisfaction and revisit intention were found to be essential mediators in this relationship. Implications: This study provides theoretical insights by integrating sustainability into halal tourism behavior models and offers practical recommendations for destination managers to develop emotionally engaging and environmentally responsible tourism services. JEL Classification: M31, O35, Q56, Z32